Wavelet analysis of static deflections for multiple damage identification in beams. (15th January 2021) - Ma, Qiaoyu; Solís, Mario; Galvín, Pedro
Highlights: Damage is located in beams from singularities in the static deflection. Wavelet local maxima are used as damage quatification features. Damage indicators are independent from damage location and external load. Multiple damage scenarios are accurately identified. Abstract: Wavelet analysis can be used in local damage detection due to its ability of revealing discontinuities induced by damage in the displacement field. This paper focuses on the application of wavelet analysis to detect and identify multiple damages using the static deflection of beams. The local damages are located by the wavelet maxima lines and their severity are evaluated from a damage index obtained from the wavelet coefficients along the corresponding maxima lines. A series of experimental tests were conducted to examine the performance of the methodology for multiple damage scenarios. The static deflections of the beam were measured by a Digital Image Correlation system. As an application, a l 1 regularization based filter is adopted to diminish the measurement noise which is critical in the application of wavelet analysis. The paper shows the capability of using wavelet analysis for closely spaced notch-type damage detection. It also analyzes the limits of the method in estimating damage with relative small severity in the presence of severe ones.